2017
DOI: 10.33866/phytopathol.029.01.0227
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Different Fungicides Against Predominant and Virulent Fungus Fusarium Nivale the Cause of Mango Malformation Disease

Abstract: Fusarium nivale (Fr.) Ces. a recently reported fungus of mango malformation disease (MMD)is a predominant and virulent fungus in mango orchards of Sindh, Pakistan. In the current study in vitro and in vivo attempts were made with commercial fungicides to reduce the severity of F. nivale. Mycelial growth of F. nivale was significantly inhibited at low and high doses of Thiophanate methyl and Fosetyl- Aluminium. Metalaxyl+Mancozeb and Mancozeb also reduced growth of fungus at their high doses (6.830 and 11.900mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Benzimidazole effectiveness against malformation was demonstrated for carbendazim, which the lower concentration assessed in vitro allowed 77% inhibition in fungus mycelial growth (MISRA;SINGH, 2002). As in this study, KHASKHELI et al(2017) found methyl-thiophanate effectiveness in Fusarium nivale control, another species causing mango malformation, in vivo and in vitro conditions. Methyl-thiophanate was the most effective along with fosetyl-Al when compared with other fungicides, such as copper fungicides, as observed in this study.…”
supporting
confidence: 69%
“…Benzimidazole effectiveness against malformation was demonstrated for carbendazim, which the lower concentration assessed in vitro allowed 77% inhibition in fungus mycelial growth (MISRA;SINGH, 2002). As in this study, KHASKHELI et al(2017) found methyl-thiophanate effectiveness in Fusarium nivale control, another species causing mango malformation, in vivo and in vitro conditions. Methyl-thiophanate was the most effective along with fosetyl-Al when compared with other fungicides, such as copper fungicides, as observed in this study.…”
supporting
confidence: 69%
“…More recently, in vitro and in vivo attempts were made with commercial fungicides to reduce the severity of Fusarium nivale (Fr.) Ces., a predominant and virulent fungus in mango orchards of Sindh, Pakistan, which was first isolated from mango MMD [38,133]. Mycelial growth of F. nivale was significantly inhibited at low doses of thiophanate-methyl and fosetyl-Aluminum.…”
Section: Fungicide Managementmentioning
confidence: 99%
“…The second spray of thiophanatemethyl and fosetyl-Aluminum fungicides completely inhibited infection of F. nivale and 100.0% reduction in vegetative malformation disease in Desi, Almas, and Dusheri, as compared to metalaxyl+mancozeb, copper oxychloride, and in control. The application of thiophanate-methyl and fosetyl-Aluminum would be useful in integrated management of MMD [133].…”
Section: Fungicide Managementmentioning
confidence: 99%